Au@Pt Nanoparticle Encapsulated Target‐Responsive Hydrogel with Volumetric Bar‐Chart Chip Readout for Quantitative Point‐of‐Care Testing1. (11th August 2014) - Zhu, Zhi; Guan, Zhichao; Jia, Shasha; Lei, Zhichao; Lin, Shuichao; Zhang, Huimin; Ma, Yanli; Tian, Zhong‐Qun; Yang, Chaoyong James
Abstract: Point‐of‐care testing (POCT) with the advantages of speed, simplicity, portability, and low cost is critical for the measurement of analytes in a variety of environments where access to laboratory infrastructure is lacking. While qualitative POCTs are widely available, quantitative POCTs present significant challenges. Here we describe a novel method that integrates an Au core/Pt shell nanoparticle (Au@PtNP) encapsulated target‐responsive hydrogel with a volumetric bar‐chart chip (V‐Chip) for quantitative POCT. Upon target introduction, the hydrogel immediately dissolves and releases Au@PtNPs, which can efficiently catalyze the decomposition of H2 O2 to generate a large volume of O2 to move of an ink bar in the V‐Chip. The concentration of the target introduced can be visually quantified by reading the traveling distance of the ink bar. This method has the potential to be used for portable and quantitative detection of a wide range of targets without any external instrument.